A case study on China's carbon emission trading system: experiences and recommendations. Issue 2 (December 2020) - Cao, Mingde
Abstract : China officially launched seven state pilot ETS programs starting in 2013 and initiated a national ETS in 2017 respectively. The many accumulated experiences from the pilot programs include such findings as the importance of setting realistic targets balancing the needs for carbon reductions with those of economic growth and pollution control and the need for legislation specifying the actions to be taken, provisions for disclosure, allowance allocations, offsets, infrastructure building, monitoring reporting and verification, and adoption of a compliance mechanism. Deficiencies in the pilot programs are evaluated, such as those derived from lack of a national legal basis and unified rules for the carbon market, an excess of free allocation of allowances, a lack of liquidity of the market, lenient punishment for non-compliance, and absence of a sound monitoring and regulatory mechanism. The requisites for sound market-based programs are described, with particular emphasis on the need for a comprehensive legal basis on which programs can be built. The pluses and minuses of cap and trade market-based programs versus carbon taxes are explored in depth, including the possibilities of combining the two systems. Various bottom up and top down approaches are explored and the key elements of success and failure.